Where Are the Women? Accounting for Discrepancies in Female Doctorates in U.S. Geography. Issue 3 (2nd July 2016) - Kaplan, David H.; Mapes, Jennifer E.
Abstract : Although there have been noticeable improvements in recent years, geography continues to be a predominantly male discipline. The percentage of women receiving PhDs in geography has tracked lower than the U.S. average of female PhDs. Previous studies of women's contribution to geography have focused on personal accounts or on the study of some of the most prominent practitioners, with a few studies using basic data on PhDs awarded and Association of American Geographers membership to determine trends. This article provides a comprehensive overview of doctoral degrees in geography by gender, over time, and across all universities in the United States by examining an alternative database, that of doctoral dissertations. The analysis yields three separate types of results. First, historical and contemporary variations among U.S. universities are examined. Second, data indicate that male and female doctoral students differ in the sex of their advisor. Third, a simple regression model explains some of the discrepancies in the proportion of female doctoral students by department. In sum, this article provides a comprehensive empirical study of the factors that might contribute to the continued disparities in female doctoral students in geography.